The efficacy of Islamic philanthropy in redressing the intricacies of economic recession in Nigeria - Muhammad, Usman Jimoh (Penerbit Universiti Kebangsaan Malaysia, 2019)
The complexity of the problems of economic recovery as it affects Nigeria is enormous not only from the perspective of its root causes, but equally from the viewpoint of its resultant effects. This makes it difficult for it to be easily addressed. Fortunately, there exists a system of Islamic philanthropy which is economic oriented for redressing the problem of economic recession in a country like Nigeria. In the interest of focus and for the purpose of synergy between the title of the paper and its content, the paper specifically examines the concept of philanthropy, economic recession and its inherent features as its affect Nigeria. Furthermore, the paper posits that in a bid to recover from the present economic predicament, the Islamic teachings on the concept of philanthropy need to be explored. This would stimulate the augmentation of governmental efforts by the well to do towards reduction of the rate of unemployment and alleviation of poverty ridden in the nation. The research adopts both descriptive and historical approach in unveiling the facts. The research concludes that the teachings of Islam on philanthropy when employed would assist towards improvement in the satisfaction of the basic needs of the people thereby emancipating the country from the yoke of economic recession. The paper recommends that a board of philanthropists be established by the government in consultation with the well to do in the society. This would be of human assistance in satisfying all aspects of needs. In addition, the composition of the board should be made up of men of integrity and probity. This would foster confidence in the minds of donors in particular and Nigerians in general.